CHARACTER BUILDING BASED ON LOCAL WISDOM IN THE FILM TITLED TANDA TANYA “?” - Nur Alfi Farikhah; Ratna Handayani Pramukti; Vena Nur Litasari; Ratna Hidayah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Character is very important in an effort to reflect cultural values that are applied through a culture of positive habits in everyday life such as honesty, trust, tolerance and caring for fellow human beings in the community. The value of local wisdom is not a barrier to progress in the global era, but still maintains cultural values that have been embedded in the surrounding community. Therefore, fostering the values of local wisdom is a strategic step in the effort to build the character of the nation. This article proposes to discuss the cultivation of cultural values through a tolerance attitude based on local wisdom in the surrounding environment as a community character reinforcement being appropriate to the cultural values which are inspired by the film titled Tanda Tanya “?”. The film describes the life that has been acculturated, then shows the assimilation and pluralism that exist in the lives of people in Indonesia. This film has educational purpose containing knowledge and learning that occur around the lives of diverse cultural communities.